Student-Faculty Research Explores Impacts of Climate Change on Agriculture in Bangladesh - Kohr, Kandace (2020)
A summer student-faculty research project has uncovered an incredible relationship between climate change, agricultural sustainability and the human condition.
Keywords: C:Bangladesh; _z:class:countries; _z:class:themes; oa:keyword:climate change; oa:sdg:2 Zero hunger; oa:topic:T10439 Adaptation to Climate Change in Agriculture; openalex:import; openalex:yes; ⛔ No DOI found